Depth-related change of sulfate-reducing bacteria community in mangrove sediments: The influence of heavy metal contamination. (March 2019) - Wu, Sijie; Li, Ruili; Xie, Shuguang; Shi, Cong
Abstract: This study provides new insight towards the effects of heavy metal contamination on sulfate-reducing bacteria (SRB) in mangrove ecosystem. We investigated SRB communities in mangrove sediments (0–30 cm depth) from Futian, Xixiang and Shajing mangrove wetlands in Shenzhen, China, with different heavy metal contamination levels. The results showed that SRB community abundance (1.71 × 10 7 –3.04 × 10 8 dsrB gene copies g −1 wet weight sediment) was depth-related and significantly correlated with Cd and Ni concentrations. The α-diversity indices of SRB community (Chao1 = 21.25–84.50, Shannon = 2.31–2.96) were significantly correlated with Cd level in mangrove sediments. Desulfobacteraceae, Desulfobulbaceae and Syntrophobacteraceae acted as major SRB groups in mangrove sediments, and Syntrophobacteraceae was most sensitive to metal contamination. UniFrace clustering analysis revealed that SRB community structure was influenced by the heavy metal concentrations. Moreover, redundancy analysis indicated that Cd and total phosphorus were the major environmental factors affecting the SRB structure in mangrove sediments. Graphical abstract: Unlabelled Image Highlights: Heavy metal pollution and sediment depth influence mangrove SRB communities. Metal concentrations affected SRB abundance, diversity and community structure. Syntrophobacteraceae was sensitive to heavy metal pollution.